Some contributions to the challenge of measuring quality of technology. (20th February 2004) - Chambers, David W.
Technology is defined as recognisable and relatively consistent patterns of getting work done situated in specific contexts and undertaken for defined purposes. A fable of technology development and transfer is presented, to set the stage for the need to be specific about what technology and transfer mean as a precondition for measuring it. This fable illustrates how the different perspectives of science, commercialisation, and political policy can clash over a single technology. A different approach is required to measure the value of technology compared to the techniques used for its development. Value and understanding are inferences about technology. Tools that are sensitive to context are offered for measuring technology. Additional tools are explored that include purpose as part of the definition of technology. These approaches go beyond metrics based on means and standard deviations and conventional statistical tests. They also have the effect of pushing the concepts of technology development and transfer closer together.